Examining The Effects of Technology Adoption, Cultural Values, Social Capital, and Government Policies on Entrepreneurial Success and Social Impact in Indonesia - Akmal, Akmal; Asriany, Asriany; Bando, Nurjannah; Mihrani, Mihrani; Mariam, Mariam (IJBLE Scientific Publications Community Inc., 2024)
This study examines the intricate dynamics of Indonesia's entrepreneurial ecosystem nexus and looks into how government policies, cultural norms, technological adoption, and social capital affect both social impact and entrepreneurial success. 350 entrepreneurs are included in a broad sample and a quantitative methodology is used. Partial least squares structural equation modeling made it easier to analyze direct and indirect links, and model fit indices confirmed that the model fit the data. The findings demonstrate how government regulations, social capital, cultural norms, and technological adoption all have a big impact on social impact and entrepreneurial success. Because all components of Indonesia's entrepreneurial ecosystem are interrelated, this study emphasizes practical lessons for entrepreneurs, politicians, and academics.